Influence of nano-silica additions on hydration characteristics and cytotoxicity of calcium aluminate as biomaterial - H.K. Abd El-Hamid; M.M. Radwan (Heliyon, 2019)
Composites of nano-calcium aluminate 'CA' biocement, synthesized by a solid state reaction, were prepared with 5, 10 and 20 wt.% of nano-SiO2 particles. The influence of nano-SiO2 particle additions on the physico-mechanical properties and hydration characteristics of CA biocement was studied. Calcium ion concentrations and, pH values of the curing medium were measured. The hydration characteristics of pure and composite CA phase were studied by determining the X-ray diffraction (XRD) and scanning electron microscopy (SEM) coupled with energy dispersive spectroscopy (EDS). Evaluation of cytotoxicity against the skin normal human cell line BJ-1 was carried out. The results showed that the bulk density and micro-hardness of the composite CA containing 10 wt.% of nano-SiO2 were better than those of pure CA and composite prepared with higher weight percentages of nano-SiO2. Both pure and composite CA bio-cements showed no cytotoxicity, making these materials suitable for medical applications.